In Silico and In Vitro Screening of Antipathogenic Properties of Melianthus comosus (Vahl) against Pseudomonas aeruginosa - Itumeleng T. Baloyi; Idowu J. Adeosun; Abdullahi A. Yusuf; Sekelwa Cosa (MDPI AG, 2021)
Bacterial quorum sensing (QS) system regulates pathogenesis, virulence, and biofilm formation, and together they contribute to nosocomial infections. Opportunistic pathogens, such as Pseudomonas aeruginosa, rely on QS for regulating virulence factors. Therefore, blocking the QS system may aid management of various infectious diseases caused by human pathogens. Plant secondary metabolites can thwart bacterial colonization and virulence. As such, this study was undertaken to evaluate three extracts from the medicinal plant, Melianthus comosus, from which phytochemical compounds were identified with potential to inhibit QS-dependent virulence factors in P. aeruginosa. Chemical profiling of the three extracts identified 1,2-benzene dicarboxylic acid, diethyl ester, neophytadiene and hexadecanoic acid as the common compounds. Validation of antibacterial activity confirmed the same MIC values of 0.78 mg/mL for aqueous, methanol and dichloromethane extracts while selected guanosine showed MIC 0.031 mg/mL. Molecular docking analysis showed anti-quorum sensing (AQS) potential of guanosine binding to CviR' and 2UV0 proteins with varying docking scores of −5.969 and −8.376 kcal/mol, respectively. Guanosine inhibited biofilm cell attachment and biofilm development at 78.88% and 34.85%, respectively. Significant swimming and swarming motility restriction of P. aeruginosa were observed at the highest concentration of plant extracts and guanosine. Overall, guanosine revealed the best swarming motility restrictions. M. comosus extracts and guanosine have shown clear antibacterial effects and subsequent reduction of QS-dependent virulence activities against P.aeruginosa. Therefore, they could be ideal candidates in the search for antipathogenic drugs to combat P.aeruginosa infections.